Memory and Conformity, but Not Competition, Explain Spatial Partitioning Between Two Neighboring Fruit Bat Colonies - Lourie, Emmanuel; Schiffner, Ingo; Toledo, Sivan; Nathan, Ran (Frontiers in Ecology and Evolution, 2021)
Spatial partitioning between neighboring colonies is considered a widespread phenomenon in colonial species, reported mainly in marine birds. Partitioning is suspected to emerge due to various processes, such as competition, diet specialization, memory, information transfer, or even "foraging cultures." Yet, empirical evidence from other taxa, and studies that tease apart the relative contribution of the processes underlying partitioning, remain scarce, mostly due to insufficiently detailed movement data. Here, we used high-resolution movement tracks (at 0. 125 Hz) of 107 individuals belonging to two neighboring colonies of the Egyptian fruit bat (Rousettus aegyptiacus), a highly gregarious central-place forager, using the ATLAS reverse-GPS system in the Hula Valley, Israel. Based on comparisons between agent-based mechanistic models and observed spatial partitioning patterns, we found high levels of partitioning of both area and tree resources (<11% overlap) that were stable across different fruiting seasons. Importantly, partitioning could not have emerged if the bats' movement was only limited by food availability and travel distances, as most commonly hypothesized. Rather than density-dependent or between-colony competition, memory, and, to a lesser extent, conformity in tree-use explain how partitioning develops. Elucidating the mechanisms that shape spatial partitioning among neighboring colonies in the wild under variable resource conditions is important for understanding the ecology and evolution of inter-group coexistence, space use patterns and sociality.